Ecza kooperatiflerinde muhasebe düzeni ve bir uygulama örneği - Güngör, Serkan (My University, 2006)
Bu çalışmada; Türkiye’de kooperatifçiliğin gelişimi incelenmiş, ardından da Ecza Kooperatifleri tanıtılarak kooperatiflerin ekonomi içerisinde ki önemi, İstanbul Ecza Kooperatifi incelenerek vurgulanmıştır. Özellikle de İstanbul Ecza Kooperatifinin finanssal faaliyetlerinin muhasebe sistemi açısından değerlendirilmesi ve raporlamada kullanılması girişi izleyen, konu ile ilgili temel kavramlar, ecza kooperatifleri ve muhasebe düzeni, uygulama, sonuç ve önerilerden oluşan beş bölümden oluşmaktadır. En son olarak ta konu ile ilgili mali değerleri belirtir tablolar sunulmuştur. İstanbul Ecza Kooperatifinin muhasebe düzeni işletmenin fonksiyonlarını rahatlıkla yerine getirebilmesi açısından önemlidir. Çünkü muhasebe mali bilgi demektir ve bilgi de günümüzde işletmeler açısından önemli bir yapı taşıdır. Bu sistemden kaynaklanacak bir noksanlık zincirin diğer tüm halkalarına zarar verir. Ecza kooperatiflerinde üyeler aynı anda müşterileri olduğundan muhasebe sistemi daha da önem kazanmaktadır.

This study analyses the developments in cooperative trading system in Turkey and introduces the Medical Cooperative Societies and emphasizes the importance of cooperative societies in the economy by focusing mainly on Istanbul Medical Cooperative Society. The evaluation of financial operations of Istanbul Medical Cooperative Society in terms of the accounting system and its use for reporting has been analyzed under five sections following the introduction part: basic terms, medical cooperative societies and accounting system, implementation, conclusion and suggestions. Finally the financial statements have been presented. The accounting system of Istanbul Medical Cooperative Society is important to allow it carry out its functions effectively. Accounting means financial information and today the information is an important building structure for enterprises. Any problem to be caused by this system will give harm to all other links in the chain. The accounting system becomes more and more important given that the members of the medical cooperative societies are the customers at the same time.
Keywords: Kooperatifler_Muhasebe